The Assessment Model "Evaluation of Math Progress based on Quantitative-Qualitative Examination and Interpretation” (VPM-EICC) in Higher Education - Pérez, Omar Mejía (2024)
The objective of this study is to evaluate the VPM-EICC evaluation model in higher education to consider or discard it as an evaluation alternative based on the impressions of those evaluated and the performance results. This evaluation model takes, as its backbone, the preparation and application of the examination instrument supported by a verification rubric, trying to qualify the criteria to shield the quantitative judgments with greater objectivity and, thus, systematize the evaluation process. The evaluation model, which was born as a necessity in high school or secondary education, is now being implemented in higher education to assess its relevance and thus have greater opportunities for applicability at different educational levels, sectors and contexts, and, thus, make it evolve towards more productive horizons. Through a mixed approach, data were collected by means of a survey and three tests, typical of a performance evaluation. Satisfactory results of relevance were found that could well promote the model as a viable and reliable alternative.